Kantian Transcendental Idealism in Physics Teaching: The Universe on a Sheet of Paper - Tiago de Jesus Santos; Esperanza Lucila Hernández Angulo; Marcelo Castanheira da Silva (Revista de Enseñanza de la Física)
One of the most attractive aspects of Theoretical Physics is that its implications are often more fascinating than ﬁction. Both Philosophy and Physics often use logical reasoning that involves experiments that cannot be carried out in practice, but that through imagination allow us to explore and understand non-experimental aspects of the Universe. Einstein popularized the term “thought experiment” for conceptual approaches explored only in the ﬁeld of ideas. In this work, we discuss how knowledge is possible through reﬂections that lead the subject from a simple logic to a transcendental logic from Kantian Transcendental Idealism. Subsequently, we present an initially simple experiment to be carried out in practice, involving folding a sheet of paper. Then, after verifying the existence of an experimental limit for its continuity, we performed it through a theoretical-mental extension and proceeded in a guided way to explore the Universe.